Inovasi Pembelajaran Pendidikan Agama Islam Berbasis Teknologi: Peran Hak Kekayaan Intelektual dan Strategi Publikasi Produk - Muhammad Rajiannor; Ani Cahyadi (Advances In Education Journal, 2026)
This study is motivated by the rapid development of information technology, which demands innovation in Islamic Religious Education (PAI) learning to make it more relevant, interactive, and aligned with learners’ characteristics in the digital era. Technology integration not only transfers materials into digital formats but also creates meaningful and contextual learning experiences. This study employs a qualitative approach with a library research design, collecting data from scientific journals, books, and relevant regulations, and analyzing them using content analysis techniques. The findings show that innovations in PAI learning include the use of interactive digital media, learning applications, and e-learning systems that enhance students’ understanding, motivation, and engagement. In addition, the protection of Intellectual Property Rights (IPR) plays an important role in maintaining originality and value, while publication strategies through journals, seminars, and digital media expand product utilization. Thus, the synergy of innovation, IPR, and publication improves the quality of PAI learning and supports adaptive, sustainable, and competitive education.